Prenatal environmental tobacco smoke exposure: a predictor of blood selenium levels in children - Gać, Paweł; Fułek, Michał; Żórawik, Aleksandra; Poręba, Rafał; Pawlas, Krystyna; Pawlas, Natalia (Frontiers in Public Health, 2025)
IntroductionThe aim of the study was to investigate the relationship between prenatal environmental tobacco smoke (ETS) exposure and blood selenium concentration (Se-B) in a selected group of children.MethodsA total of 299 children were recruited for this study. Prenatal ETS exposure (understood as active as well as passive mother’s exposure) was assessed among all the study participants using a standardized exposure scale. The participants were tested for Se-B.Results and discussionSe-B (μg/L) was statistically significantly lower in the group of children with prenatal exposure to ETS compared to those without prenatal exposure (74.35 ± 12.45 vs. 78.60 ± 11.66, p < 0.01). Similarly, children whose mothers actively smoked tobacco during pregnancy exhibited lower Se-B than children whose mothers did not smoke (72.09 ± 14.20 vs. 77.58 ± 11.70, p < 0.05), and a similar trend was observed for passive smokers (74.63 ± 12.35 vs. 78.40 ± 11.75, p < 0.01). While negative correlations were observed between the severity of ETS exposure and Se-B, these results were not statistically significant. Independent risk factors for lower Se-B included advanced age (Rc: −2.398, p < 0.05), body weight deficiency (Rc for lower body mass index within the range of underweight to normal body weight: 0.687, p < 0.05), and prenatal ETS exposure (Rc: −4.209, p < 0.05). This study highlights the association between maternal tobacco smoke exposure during pregnancy and reduced selenium levels in offspring, emphasizing the importance of targeted interventions in prenatal care to minimize ETS exposure.